“Why not ask the doctor?” Barriers in help-seeking for sexual problems among older adults in Poland - Gore-Gorszewska, Gabriela (Int J Public Health, 2020)
OBJECTIVES: Existing data show that older adults rarely seek medical or psychological help for their sexual problems. The current study explores the barriers in help-seeking faced by older adults from a conservative Central European country. METHODS: Thirty semi-structured interviews were conducted among Polish residents (16 women, 14 men) aged 65–82. The data were analysed thematically, with coding validity and analytical rigour ensured throughout the process. RESULTS: Three main barriers in seeking help were identified: not recognising sexual problems; fear for the doctors’ disapproval; lack of knowledge how to access appropriate services. The data reveal that the participants’ main concern is that health providers would dismiss their problems as trivial. Older adults from Poland suffer from the lack of fundamental knowledge about their sexual functioning. CONCLUSIONS: Employing qualitative methodology to understand why older adults from conservative cultures do not seek help for their sexual problems might contribute to existing literature by providing evidence from different cultural settings, and help to develop and implement appropriate interventions. Implications related to health providers’ attitude towards older patients’ concerns are further discussed. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00038-020-01472-6) contains supplementary material, which is available to authorised users.